The general history of Polybius / translated from the Greek by Mr. Hampton. - Polybius. (Tufts University. Tisch Library., 2015)
Volume 4 of 4.; 1 online resource (2 volumes); Often found with octavo issue of vol. 1-2, 3rd. edition, 1772.; Tufts print copy: vol. 3-4 found with octavo issue of vol.1-2, 2nd. edition, 1761.; Includes index.; Binding: Tufts print copy: Half bound in later green leather; gilt lettering to spine.; Indexed in: English Short Title Catalog, N18349